KEGUNAAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) - Tita Rachmawati (Applied Business and Administration Journal, 2022)
In a competitive market competition, a company needs to maintain positive relationships with customers. This is because customers are the key to the success of a business, without customers, a business will not be possible to keep running. The existence of a good CRM (Customer Relationship Management) program can help companies provide satisfaction to customers. In this article, what we will find out is about the influence of CRM in maintaining and providing satisfaction to customers. In addition, CRM can also help companies increase market share, productivity, and superior employee morale by increasing customer knowledge and also higher customer satisfaction to increase customer loyalty. As a provider of satisfaction, companies will also have clearer information about who their customers are, what their needs are, and what will make them more satisfied.